Pengarusutamaan Integrasi Keilmuan Islam dan Sains di Lembaga Pendidikan Islam: Tinjauan Baru Menuju Islam Berkemajuan - Rusmawati, Putri (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
The findings of this study reveal several salient points. Firstly, the integration of Islam and science serves as a conduit for harmonizing religious principles with scientific inquiry, preserving the integrity of both domains while fostering unity. Secondly, the relationship between religion and science is depicted as complementary, wherein religion nurtures scientific inquiry while science corroborates the divine revelations of Allah SWT. Furthermore, the relationship between Islam and science is delineated through four distinct approaches: conflict, independence, dialogue, and integration. This multifaceted engagement underscores the dynamic interaction between religious and scientific paradigms. Moreover, the scientific integration of Islam and science underscores the burgeoning influence of scientific discoveries on civilization. Numerous Muslim scholars have contributed novel insights derived from Western scientific advancements, which are subsequently imbued with Islamic values, thus enriching the intellectual landscape and fostering progressive Muslim thought. In conclusion, the ongoing dialogue and integration between Islam and science signify a nuanced and evolving relationship, characterized by mutual enrichment and dynamic engagement. By integrating scientific advancements with Islamic teachings, Muslims are poised to cultivate an enlightened worldview that embraces both spiritual values and scientific progress, thereby advancing societal development and intellectual discourse.